Impacts of landscape-scale forest loss and a dry event on the demographic structure of the endangered palm Euterpe edulis Mart. in the Atlantic Forest - Leal, Adrielle; Benchimol, Maíra; Costa, Hugo C. M.; Faria, Deborah; Cazetta, Eliana (Frontiers in Forests and Global Change, 2022)
Forest loss is one of the most serious threats to biodiversity in the tropics and mainly occurs due to the conversion of native forests by the expansion of human activities. In addition, regional climate change is likely to adversely affect the remaining biota. These disturbances may have direct or indirect consequences on the demographic structure of plant species in human-modified landscapes. To test this hypothesis, and thus look for management practices aimed at enhancing the population viability, we used the palm species Euterpe edulis Mart. (Arecaceae) to assess the demographic structure of five ontogenetic stages prior (2014) and after (2017) a prolonged drought event (2015) that occurred in the northeastern Atlantic Forest of Brazil. We also investigated the influence of landscape forest cover on the ontogenetic demographic structure, given that forest remnants were embedded within landscapes ranging from 6 to 97% of forest amount. We revealed that forest cover was a key predictor explaining the abundance patterns of E. edulis, with all ontogenetic stages (except seedlings, immature, and adults) exhibiting lower abundance in forest remnants surrounded by lower amount of native forests. Conversely, the regional drought event unaffected the demographic structure of this palm species, which may suggest that populations of E. edulis were able to cope with an isolated, though severe, drought event. The impacts of forest loss on E. edulis demographic structure, particularly on juveniles, raises a concern about the future persistence of E. edulis populations, since the early stages represent the adult generation in the near future. Management measures, including species reintroduction, forest restoration, environmental education programmes and the enforcement of environmental laws must be encouraged to safeguard E. edulis populations in the Atlantic Forest.